Pengembangan Media Pembelajaran Kahoot Pada Materi Kimia Minyak Bumi Kelas XI di MA Darunnajah Duman - Hidayatul Laelin; I Nyoman Loka; Burhanuddin Burhanuddin (Chemistry Education Practice, 2026)
The aim of this research is to produce Kahoot learning media on petroleum material with minimum feasible criteria based on validity, practicality and effectiveness. This type of research uses research and development procedures. The development model used is the 4-D model developed by Thiagarajan et al (1974). In this research, the Kahoot learning media was developed, media validated by 3 people, namely 2 Chemistry Education lecturers and 1 chemistry subject teacher as well as all 23 class XI MIA students to test the practicality and effectiveness of the Kahoot media being developed. . The results of the validity test with Aiken's V show an average value of 0.83 with a very valid category, which means very feasible. The results of the practicality test using a Likert scale obtained an average value of 83.5%, which indicates a very practical category, which means very feasible. The results of the effectiveness test using the n-gain test obtained a percentage of 77% in the effective category, which means very feasible.